Transdural retrieval of a retropulsed lumbar interbody cage: Technical case report - Zaidi, Hasan; Shah, Ashish; Kakarla, Udaya (Asian Journal of Neurosurgery, 2016)
The purpose of this case report was to describe a novel method to retrieve a herniated lumbar interbody cage. Transforaminal lumbar interbody fusion (TLIF) is an increasingly popular method of spinal fixation and fusion. Unexpected retropulsion of an interbody is a rare event that can result in intractable pain or motor compromise necessitating surgical retrieval of the interbody. Both anterior and posterior approaches to removing migrated cages may be associated with significant surgical morbidity and mortality. A 60-year-old woman underwent an L4-S1 TLIF coupled with pedicle screw fixation at a previous hospital 5 years prior to admission. She noted sudden-onset bilateral lower extremity weakness and right-sided foot drop. Magnetic resonance imaging and radiographs were notable for purely centrally herniated interbody. A posterior, midline transdural approach was used to retrieve the interbody. Situated in between nerve rootlets to the ventral canal, this virgin corridor allowed us to easily visualize and protect neurological structures while safely retrieving the interbody. The patient experienced an immediate improvement in symptoms and was discharged on postoperative day 3. At 12-month follow-up, she had no evidence of cerebrospinal fluid (CSF) leak and had returned to normal activities of daily living. While the risk of CSF leak may be higher with a transdural approach, we maintain that avoiding unnecessary retraction of the nerve roots may outweigh this risk. To our knowledge, this is the first case report of a transdural approach for the retrieval of a retropulsed lumbar interbody cage.
Keywords: Cage migration; lumbar interbody; transdural approach